Metodología para el diseño de un índice de condiciones de vida para los adolescentes jóvenes (2008)
ABSTRACT: To provide information about life conditions among young adolescents who are 15-19 years of age, and who live in the urban area of Medellin, Colombia based on different qualification of live domains and indicators analyzed through a hierarchical model. Materials and methods: a cross-sectional study was conducted in a representative random sample of 1.066 youths who were surveyed with a questionnaire validated by appearance and contents. The questionnaire contained conceptual domains about youth’s life conditions. After the data collection process the optimal scaling technique on data for qualitative variables in order to select principal component was performed. The first principal component was chosen as the Youth’s Life Conditions Index (ylci). The relevancy of the requirements included in the procedure was previously checked. The index we standardized so as their results would vary according to a scale o 0 to 100 points. Once the ylci was validated, its results were described in a general way according to age, sex, socioeconomic level, and residence area. A multilevel model was built with the individual and contextual variables that better explain the applied index. Results and conclusions: the lci showed an average of 57.7, which was higher in women; the average lci increased according to higher socioeconomic level and it diminished when age was increased in one year. The lowest lci was obtained from youths living in northeastern and northwestern areas of the city. According to the multilevel analysis pattern, the unemployment rate as a contextual variable in the neighborhood was important in decreasing the lci. The results suggest that it is necessary to perform a monitoring process of inequalities in the life conditions of young adolescents, especially in those areas of the city with very depressed social-economic levels.